Development of element model subroutines for implicit and explicit analysis considering large deformations. (October 2020) - Tian, Hao; Li, She; Cui, Xiangyang
Highlights: A Smoothed Galerkin weak form framework is presented for implicit and explicit solvers. ES-FEM has been embedded into the commercial software ABAQUS by user defined element subroutines (UEL/VUEL). Detailed procedures for implementation of UEL and VUEL are developed. Practical engineering problems considering large deformation are solved by UEL and VUEL. Abstract: In this work, an edge-based smoothed finite element method (ES-FEM) is embedded into the commercial software ABAQUS by using user defined element subroutines (Implicit/UEL, Explicit/VUEL). Unstructured meshes (i.e. triangular and tetrahedral elements) are employed in the framework due to their good geometric adaptability and the advantages of being automatically generated in the software. In ES-FEM, smoothing domains are further constructed associated with edges of triangular or tetrahedral elements. Linear and no-linear material models are included for static, free vibration, and large deformation analysis. Several numerical examples for predicting displacements, eigenvalues, and forging forming process are implemented. Results illustrated that the ES-FEM by using UEL and VUEL presents preciser than traditional finite element method (FEM), temporally stable, and can overcome the difficulties such as mesh distortion when the FEM is solving large deformation problems such as forging. It is valuable to embed the excellent numerical models, for example ES-FEM, into the commercial software since engineers can use it conveniently without professional knowledge. In this work, the detailed procedures are provided for the implementation of ES-FEM in UEL and VUEL, including pre-processing, post-processing and subroutine writing processes.